Chamber study on the migration of di-n-octyl phthalate (DNOP) between source surfaces and settled dust: Influence of temperature and dust loading. (1st January 2022) - Li, Ao; Liu, Cong; Kang, Lingyi; Liu, Ke; Wang, Xinke
Abstract: Phthalates (PAEs) are pervasive in indoor environments. In this study, two migration pathways of di-n-octyl phthalate (DNOP) from a source to dust were investigated using microchambers in a thermostatic incubator: (1) mass transfer through direct contact with source surfaces; (2) mass transfer through air. A 20-day emission experiment with settled dust was performed at 30 °C. Significantly higher concentrations were observed in dust that was in direct contact than in dust that was not, which indicated that direct contact enhanced the sorption of the dust on DNOP. The difference between source and non-source surface was low of the migration of the DNOP in the dust. In addition, the temperature and dust loading and diffusion distance were considered. The results suggested that the temperature did not considerably influence the difference between source and non-source surface; however, the difference increased with an increase in dust loading. These results can help understand the mass transfer mechanism of PAEs to implement effective control measures and reduce the human exposure to PAEs in indoor environments. Graphical abstract: Image 1 Highlights: Direct contact played an important role in migration of DNOP from source to dust. Contribution of direct contact of the migration was not extremely high. Migration via air in the boundary level should not be neglected. Temperature has little influence on the difference between source and non-source surface. Dust loading had a positive correlation with the difference between source and non-source surface.